2015
DOI: 10.32734/jtk.v4i1.1458
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH SUHU REAKSI DAN JUMLAH KATALIS PADA PEMBUATAN BIODIESEL DARI LIMBAH LEMAK SAPI DENGAN MENGGUNAKAN KATALIS HETEROGEN CaO DARI KULIT TELUR AYAM

Abstract: Biodiesel is an alternative fuel for diesel engines consisting of the alkyl monoesters from vegetable oils or animal fats. Beef tallow waste is the non-edible raw material with low cost production and the availability is huge in the cattle production. The objective of the study was to utilize beef tallow waste for biodiesel production using solid oxide catalyst which derived from the industrial eggshells. The materials calcined with temperature 900oC and time 2 hours, transformed calcium species in the shells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
3
0
3
Order By: Relevance
“…The transesterification reaction that is given a treatment of increasing catalyst amount showed there was a problem in the contact (collision) between molecule, because the given catalyst would precipitate and coagulate in the base of reaction gourd. This statement was proven by Wendi et al (2015) who stated that the effect of the increase of catalyst amount, the combination of catalyst and reactant had become too thick, so it cause trouble in the mixing and demanding of higher power consumption for the mixing. The problem would also affect the catalytic activity from the used catalyst decreased as the decreasing of catalyst active side function, and the adsorption process of reactant molecules in the catalyst active surface would be disturbed by the precipitation problem of the given catalyst (Arita et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The transesterification reaction that is given a treatment of increasing catalyst amount showed there was a problem in the contact (collision) between molecule, because the given catalyst would precipitate and coagulate in the base of reaction gourd. This statement was proven by Wendi et al (2015) who stated that the effect of the increase of catalyst amount, the combination of catalyst and reactant had become too thick, so it cause trouble in the mixing and demanding of higher power consumption for the mixing. The problem would also affect the catalytic activity from the used catalyst decreased as the decreasing of catalyst active side function, and the adsorption process of reactant molecules in the catalyst active surface would be disturbed by the precipitation problem of the given catalyst (Arita et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of percentage from the products area in the use of 5% catalyst shows that there is a problem in the collision between molecules because the catalyst was deposited and thickened in three-neck flask. Wendi et al, (2015) reported that the number of catalyst make the obstruction of contact between oil and methanol resulting the decrease of biodiesel conversion on the 3% to 4% catalyst amount percentage. The decrease of biodiesel conversion was also caused by the reaction between catalyst and oil which blocked the contact between oil and methanol.…”
Section: Resultsmentioning
confidence: 99%
“…Oleh sebab itu, penggunaan energi yang berbasis bahan bakar asal fosil perlu dikurangi dengan cara mengoptimalkan penggunaan energi yang terbarukan dan mengurangi subsidi bahan bakar minyak. Indonesia memiliki banyak sumber daya alam hayati yang dapat dimanfaatkan sebagai bahan baku bioenergi (biodiesel) [3]. Di Indonesia minyak solar merupakan bahan bakar yang sering digunakan, namun untuk menekan tingkat penggunaan bahan bakar tersebut dengan penggantian ke biodesel [4].…”
Section: Pendahuluanunclassified